DAMPAK KEBIJAKAN LAND REFORM TERHADAP PINJAMAN LUAR NEGERI ZIMBABWE KEPADA IMF TAHUN 2008 - ", Medriamel; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This is a political economic studies in international relations which describes about the impact of land reform policies towards foreign loans to the IMF in 2008.Robert Mugabe's land reform policies have a negative impact on the economy in Zimbabwe. Land reform policy are made to take land owned by white farmers forcibly and given to supporters political party of Robert Mugabe. Land reform policies decrease economic growth and suffered hyperinflation and the result IMF suspended aid to Zimbabwe's foreign loans. This researchpurpose to explain the impact of land reform policies towards foreign loans to the IMF in 2008 and describes the effect on the economy Zimbabwe, the object of this study is the policy of land reform in Zimbabwe. This is qualitative research which used descriptive methods, and collecting data from books, journals, official publications and relevant websites. This paper used the behavioralist perspective and international economic cooperation theory proposed by Anne Kruenger, Deepak Lal. The result of this research shows that Hyperinflation in Zimbabwe bring bad influence on society and the IMF decided to make economic aid to Zimbabwe Zimbabwe is getting worse. However zimbabwe tried to growby making changes such as dollarization, and use of loan funds to effectively lead the IMF to revoke suspension of aid funds to Zimbabwe.Keyword : Land Reform Policy , IMF, Economic of Zimbabwe